2017
DOI: 10.1186/s13037-017-0131-3
|View full text |Cite
|
Sign up to set email alerts
|

Surgical site infection and its associated factors following cesarean section: a cross sectional study from a public hospital in Ethiopia

Abstract: BackgroundA cesarean section is a surgical procedure in which incisions are made through a woman's abdomen and uterus to deliver her baby. Surgical site infections are a common surgical complication among patients delivered with cesarean section. Further it caused to increase maternal morbidity, stay of hospital and the cost of treatment.MethodsHospital based cross-sectional study was conducted to assess the magnitude of surgical site infection following cesarean Site Infections and its associated factors at L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
76
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(93 citation statements)
references
References 10 publications
14
76
3
Order By: Relevance
“…Among these, 705 disregarded due to qualitative study, abstracts, conference abstracts, and titles. Of 15 eligible studies, identified for SSI were 13 studies [14,15,[23][24][25][26][27][28][29][30][31][32][33] with 7786 study participants. Studies identified for pathogens were Five studies [15,25,28,34,35] with 629 subjects.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Among these, 705 disregarded due to qualitative study, abstracts, conference abstracts, and titles. Of 15 eligible studies, identified for SSI were 13 studies [14,15,[23][24][25][26][27][28][29][30][31][32][33] with 7786 study participants. Studies identified for pathogens were Five studies [15,25,28,34,35] with 629 subjects.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…These five studies conducted on patients who already developed surgical site infections. Finally, this meta-analysis includes a total of 15 studies with 8418 subjects [14,15,[23][24][25][26][27][28][29][30][31][32][33][34][35] (Fig. 1).…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations